Dermoscopic features of children scabies - Nie, Ying-li; Yi, Hong; Xie, Xiao-yan; Fu, Gui-li; Zheng, Yuan-quan (Frontiers in Medicine, 2023)
Scabies is a common skin disorder, caused by the ectoparasite Sarcoptes scabiei. The scabies mites burrow is highly diagnostic but illegible by the naked eye, because it is tiny and may completely be obscured by scratch and crust. The classic technique is opening the end of an intact mite burrow with a sharp instrument and inspecting its contents in the light microscope under loupe vision. Dermatoscope is a new method to diagnose scabies, with the advantages of noninvasive and more sensitive. This study verified the characteristic manifestations of scabies under dermoscopy. Under the closer examination of the curvilinear scaly burrow, the scabies mite itself may be seen as a dark equilateral triangular structure, which is often referred to as a “jet with contrail”. Besides, this study found that the positive detection rate of microscopic characteristic manifestations under the dermoscopy orderd by the external genitals, the finger seams and the trunk, which were statistically different (P-value < 0.05). Of note, this is the first study to explore the regional distribution of the characteristic dermoscopic manifestations of scabies. We are the first to propose to focus on examining the external genitalia and finger seams with dermoscopy.